A comparative analysis of driving force models for fatigue crack propagation of CFRP-reinforced steel structure. (January 2020) - Ye, Huawen; Wang, Tianqi; Wu, Chuangjie; Duan, Zhichao; Liu, Changmeng
Highlights: Several typical crack driving force models are described and verified experimentally at various stress ratios ( R -ratios). Two driving force model using K max and Δ K eff is recommended in a large scope of R -ratios and loading patterns. Abstract: A comparative analysis is carried out on the fatigue mechanism of damaged steel structures reinforced with non- and prestressed CFRP (Carbon Fiber-reinforced Polymer). Several typical crack driving force models are described and verified at various stress ratios ( R -ratios) through extensive fatigue crack growth data taken from literature. The fatigue tests of various steel elements and corresponding finite element method modeling are used to verify crack growth rate correlation and life prediction accuracy. The results prove that the two driving force model using K max and Δ K eff can provide an accurate life prediction in a large scope of R -ratios and loading patterns.